C1q/TNF-Related Protein 9 Inhibits Coxsackievirus B3-Induced Injury in Cardiomyocytes through NF-κB and TGF-β1/Smad2/3 by Modulating THBS1 - Kebei Liu; Juan Wang; Xinru Gao; Wei Ren (Mediators of Inflammation)
C1q/TNF-related protein 9 (CTRP9) is implicated in diverse cardiovascular diseases, but its role in viral myocarditis (VMC) is not well explored. This study is aimed at investigating the role and potential mechanism of CTRP9 in VMC. Herein, we found that the peripheral blood collected from children with VMC had lower CTRP9 levels than that from children who had recovered from VMC. H9c2 cardiomyocytes treated with coxsackievirus B3 (CVB3) were applied to establish a VMC model in vitro, and the expression of CTRP9 was significantly decreased in CVB3-induced H9c2 cells. The overexpression of CTRP9 attenuated CVB3-induced apoptosis, inflammation, and fibrosis reactions in H9c2 cells by promoting cell proliferation, reducing the cell apoptosis rate, and inhibiting inflammatory cytokine levels and fibrosis-related gene expression. Moreover, we found that thrombospondin 1 (THBS1) levels were increased in children with VMC, and CTRP9 negatively regulated THBS1 expression by interacting with THBS1. The downregulation of THBS1 inhibited CVB3-induced apoptosis, inflammation, and fibrosis in H9c2 cells. In addition, our mechanistic investigation indicated that the overexpression of THBS1 impaired the inhibitory effect of CTRP9 on CVB3-induced H9c2 cells. The results further revealed that the CVB3-induced NF-κB and TGF-β1/Smad2/3 signaling pathways of H9c2 cells were blocked by CTRP9 yet activated by THBS1. In conclusion, CTRP9 protected H9c2 cells from CVB3-induced injury via the NF-κB and TGF-β1/Smad2/3 signaling pathways by modulating THBS1.